Nickel Removal By Adsorption Using Oil Palm Fibre. - Isa, M. Hasnain; Aziz, Hamidi A.; Asaari, Faridah A. H.; Abustan, Ismail (Universiti Sains Malaysia, 2009)

(untitled)
Nickel (Ni) is present in waste waters of a number of industries e.g. steel, electroplating, batteries manufacture, etc. Conventional heavy metal removal technologies such as ion exchange, chemical precipitation, reverse osmosis, etc. are often ineffective or expensive.